The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1038/srep05318
|View full text |Cite
|
Sign up to set email alerts
|

Lp(a) is not associated with diabetes but affects fibrinolysis and clot structure ex vivo

Abstract: Lipoprotein (a) [Lp(a)] is a low density lipoprotein (LDL) with one apolipoprotein (a) molecule bound to the apolipoprotein B-100 of LDL. Lp(a) is an independent risk factor for cardiovascular disease (CVD). However, the relationship of Lp(a) to diabetes and metabolic syndrome, both known for increased CVD risk, is controversial. In a population based study on type two diabetes mellitus (T2DM) development in women, Lp(a) plasma levels showed the well known skewed distribution without any relation to diabetes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…correlations between Lp(a) levels and the inhibition of plasma clot lysis in vitro with Lp(a)-lowering hormone replacement therapy (30) or in the setting of disorders such as residual vein obstruction and cerebral venous sinus thrombosis (31), or myocardial infarction (32). In another study, it was found that patients with type 2 diabetes mellitus had longer clot lysis times than healthy control subjects, although no difference in lysis time by quartile of Lp(a) levels was found in either group (33). Our study has an The lack of effect of purified Lp(a) on clot lysis is surprising in light of an extensive body of evidence that apo(a) itself inhibits fibrinolysis and plasminogen activation (6).…”
Section: Discussionmentioning
confidence: 99%
“…correlations between Lp(a) levels and the inhibition of plasma clot lysis in vitro with Lp(a)-lowering hormone replacement therapy (30) or in the setting of disorders such as residual vein obstruction and cerebral venous sinus thrombosis (31), or myocardial infarction (32). In another study, it was found that patients with type 2 diabetes mellitus had longer clot lysis times than healthy control subjects, although no difference in lysis time by quartile of Lp(a) levels was found in either group (33). Our study has an The lack of effect of purified Lp(a) on clot lysis is surprising in light of an extensive body of evidence that apo(a) itself inhibits fibrinolysis and plasminogen activation (6).…”
Section: Discussionmentioning
confidence: 99%
“…Apo(a) by its similarity to plasminogen can competitively inhibit the functioning of this zymogen and hence increase the risk of atherosclerotic vascular disease. The similarity of Lp(a) to LDL and its ability to undergo oxidation are another reason why it has been implicated in atheroma development and has been suggested to be involved in foam cell formation, smooth cell proliferation, endothelial dysfunction, and vascular inflammation [9, 10]. Several epidemiological studies have found clear association between Lp(a) and CVD and have suggested Lp(a) to be an independent risk factor for CVD [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Rowland et al found that the LPA genetic variant rs3798220 was associated with decreased clot permeability and longer clot lysis time among Caucasians, but was associated with increased clot permeability and shorter clot lysis among non-Caucasians (Rowland et al 2014). Mansson et al however, reported that Lp(a) plasma levels had no effect on clot lysis time in diabetic subjects and normal controls (Mansson et al 2014). These discordant results may be caused by: (1) differing study designs; (2) different measure methods; (3) small sample size; and/or (4) differences in population characteristics.…”
Section: Discussionmentioning
confidence: 99%